Factors influencing coffee purchase intention among generation Z in Malaysia - Chan, Emily Kai An (2023)
Coffee is a beverage that is common and popular, consumed by people around the world. Malaysian coffee consumption has increased, as the result of urbanisation and Western culture that have influenced the Malaysian lifestyle. Many coffee shops or cafés such as Starbucks, The Coffee Bean, The Leaf, and etc were introduced and expanded rapidly in Malaysia. More new cafés with different theme, designs, and styles were introduced in Malaysia and indirectly makes coffee became a regular drink among Generation Z in Malaysia. Thisresearch is to study the factors influencing coffee purchase intention among Generation Z. It consists of five independent variables namely elitism, health, socialisation, culture, and hedonism, while the dependent variable is coffee purchase intention. 408 data collected using online survey and tested using SPSS. The result of the study also shows that four independent variables are supported which are elitism, health, culture, and hedonism. While, have one independent variable is unsupported which is socialisation. Lastly, the finding provides the coffee industry and people with information or knowledge about Generation Z coffee purchase intention.